Improving community-based first response to out of hospital cardiac arrest (FirstCPR): protocol for a cluster randomised controlled trial - Sandra Ware; Blake Angell; Julie Redfern; Clara Chow; Cate Ferry; Lee Taylor; Christopher Semsarian; Adrian Bauman; Janet E Bray; Simone Marschner; Michael Nelson; Saurabh Kumar; et al. (BMJ Open)
Introduction Out-of-hospital cardiac arrest (OHCA) is associated with poor survival outcomes, but prompt bystander action can more than double survival rates. Being trained, confident and willing-to-perform cardiopulmonary resuscitation (CPR) are known predictors of bystander action. This study aims to assess the effectiveness of a community organisation targeted multicomponent education and training initiative on being willing to respond to OHCAs. The study employs a novel approach to reaching community members via social and cultural groups, and the intervention aims to address commonly cited barriers to training including lack of availability, time and costs.Methods and analysis FirstCPR is a cluster randomised trial that will be conducted across 200 community groups in urban and regional Australia. It will target community groups where CPR training is not usual. Community groups (clusters) will be stratified by region, size and organisation type, and then randomly assigned to either immediately receive the intervention programme, comprising digital and in-person education and training opportunities about CPR and OHCA over 12 months, or a delayed programme implementation. The primary outcome is self-reported ‘training and willingness-to-perform CPR’ at 12 months. It will be assessed through surveys of group members that consent in intervention versus control groups and administered prior to control groups receiving the intervention. The primary analysis will follow intention-to-treat principles, use log binomial regression accounting for baseline covariates and be conducted at the individual level, while accounting for clustering within communities. Focus groups and interviews will be conducted to examine barriers and enablers to implementation and costs will also be examined.Ethics and dissemination Ethical approval was obtained from The University of Sydney. Findings from this study will be disseminated via presentations at scientific conferences, publications in peer-reviewed journals, scientific and lay reports.Trial registration number ACTRN12621000367842.